Pelaksanaan Matrikulasi Untuk Meningkatkan Penguasaan Operasi Hitung Dasar Matematika Siswa SMKN 2 Langsa - Ibnu Zaina; Rahmah Johar; Saminan Saminan (Universitas Syiah Kuala, 2019)
Student mastery of the basic arithmetic operations of mathematics is still low, especially for students who received school education background before heterogens. This research was conducted to determine the type of error that made the students in doing mathematics basic arithmetic operations, increase students' ability to perform basic arithmetic operations through the implementation of the mathematics matriculation, and suitability scores obtained by students with a score of predetermined targets. This research is a descriptive qualitative research subjects were 27 students of class X SMK 2 Langsa. Data were analyzed using the concept of Miles and Huberman: includes the step of data reduction, data presentation, and conclusion. The results showed that the errors made by the students in solving basic math arithmetic operations are procedural and conceptual errors. Procedural errors do end results is a mistake, an error in the operations of addition, subtraction, multiplication, and division of integers. Conceptual error committed is a mistake to equate the denominator in the operation of addition and subtraction of fractions, simplifying error in root form, and errors in rationalizing the denominator.